Machines that think : everything you need to know about the coming age of artificial intelligence (Boston, MA : Nicholas Brealey Publishing, 2022)
""Machines That Think" is your guidebook to the AI revolution. Discover how artificial intelligence will change the world, meet machines that compose music and write stories, and face the ultimate question: is AI really a threat?"--Provided by publisher.
Includes bibliographical references (page 259) and index.
Keywords: Artificial intelligence -- Popular works; Robotics -- Popular works; Popular works